Dinamika Kemiskinan Regional di Provinsi Sulawesi Utara: Bukti Empiris Berbasis Data Panel - Syifaur Rahmah; Aditya Kumala Dewi; Reni Eka Septiani; Naswatun Zikra (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Poverty remains a complex development issue and continues to be a critical problem in Indonesia. This study aims to examine the effects of population size, life expectancy, mean years of schooling, and the open unemployment rate on poverty levels. The research employs a quantitative approach using panel data regression with the Fixed Effect Model (FEM). The analysis is based on secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik), covering 15 regencies/cities over the period 2017–2023, resulting in a total of 105 observations. The findings indicate that all independent variables simultaneously have a significant contribution to poverty levels. Partially, population size and the open unemployment rate show a significant positive relationship with poverty. In contrast, quality-of-life variables, represented by life expectancy and mean years of schooling, have a significant negative effect on poverty levels. These results suggest the importance of an integrated development strategy that emphasizes improving access to education and healthcare, managing population dynamics, and expanding employment opportunities in order to reduce poverty sustainably.